How do muscle injuries relate to return-to-performance metrics in male elite football players? - Guitart, M.; Alonso-Callejo, A.; Rodas, G.; Cos, F.; Martin-Garcia, A.; Franquesa, X.; Carles, B.; Valle, X.; Yangüas, X.; Felipe, J. L. (Biology of Sport, 2026)
The aim of this study was to analyze how the type, location, and severity of injury are associated with the time elapsed since the return to training and matches of male football players to reach fitness values comparable to pre-injury levels. A longitudinal analysis was conducted on 333 male football players from an elite Spanish football club over five seasons (2017/18 to 2021/22). A total of 234 injuries (including medical attention) were included in the analysis. The study focused on hamstring and quadriceps injuries, examining high-speed running, sprint distance, and maximum velocity before and after injury. Results indicated that hamstring injuries significantly impact Vmax and HSR, with severe injuries requiring up to five weeks to return to pre-injury levels (Vmax: -1.43 km/h, p = 0.01; HSR: -32.90 m, p = 0.04). Quadriceps injuries revealed less impact on performance metrics than hamstring injuries, with only mild injuries resulting in a significant reduction in Vmax (-1.18 km/h, p = 0.04) and HSR (-52.70 m, p = 0.01) during the first week post-injury. The findings highlight the importance of injury-specific rehabilitation protocols and the need for tailored training loads to minimise the risk of re-injury and optimise return to performance. This research provides valuable insights for medical and performance staff in elite football, emphasizing the critical role of injury management in maintaining player performance and club success.